Quotes and Images From The Works of George Meredith - Meredith, George, 1828-1909; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2004)
"Quotes and Images From The Works of George Meredith" by George Meredith is a collection that showcases selected quotes and illustrations from the esteemed Victorian-era author, poet, and novelist. This book, likely compiled in the early 20th century, encapsulates Meredith's keen observations on life, love, and the human condition, reflecting the complexities of personal relationships, societal norms, and philosophical musings prevalent in his writings. The content of the book presents a rich tapestry of Meredith's thoughts articulated through aphorisms and reflections. Each quote is laden with insight, revealing his astute commentary on themes such as feminine nature, the pitfalls of romantic relationships, and the nuances of human behavior. The collection not only serves as a testament to his literary genius but also acts as a mirror reflecting the societal context of his time, engaging readers with both familiar and thought-provoking perspectives that remain relevant even today. These crafted statements invite contemplation and encourage a deeper understanding of the intricate layers of human emotion and societal structure. (This is an automatically generated summary.)
Release date is 2004-08-29
Produced by David Widger
Keywords: Quotations